PENDIDIK SEBAYA SEBAGAI UPAYA PENCEGAHAN BAHAYA MEROKOK PADA REMAJA DI PONTIANAK - Abduh Ridha (Jurnal Buletin Al-Ribaath, 2016)
High smoking prevalence in Pontianak, especially youngsters, was majorly affected by lack of knowledge. Therefore, this community services activity was aimed to improve knowledges and attitudes of peer educators about smoking hazard and strengthen the role of peer educators to increase knowledge and attitude of their groups. One group pretest-posttest was used to evaluate the success of community service activities. The analysis was conducted using T test to look at the relationship of each independent variable on the dependent variable. Results showed there were increased knowledge and attitudes peer educator after training. There were also an increased knowledge and attitudes of studeents after the peer group mentoring. There are differences in knowledge and attitudes among the peer group and the control group. Selection of a facilitator with the appropriate background, as well as the preparation of training materials and tools that support the training process. Key words: adoloscene, peer educators, peer group, knowledge, attitude